Penatalaksanaan Pasien Perempuan Usia 33 Tahun dengan Infeksi Saluran Kemih dan Dispepsia melalui Pendekatan Dokter Keluarga di Wilayah Puskesmas Rawat Inap Kedaton - Anjaya, Putri Ulayya; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2024)
Urinary tract infection (UTI) is an infection caused by the growth of microorganisms in the urinary tract that causes inflammation and bacteriuria. It is estimated that there are around 150 million cases of UTIs occurring each year worldwide, which can burden health care expenditures. Dyspepsia is a group of symptoms that include uncomfortable sensations in the abdomen, such as pain, bloating, nausea, and vomiting. It is estimated that almost 30% of cases encountered in general practice and 60% in gastroenterology practice are dyspepsia. Implementing comprehensive and holistic family doctor services by identifying risk factors, clinical problems, and patient management based on evidence-based medicine with a patient-centered, family approach and community-oriented strategy. This study is a case report. Primary data were obtained through anamnesis, physical examination and home visits. Secondary data were obtained from the patient's medical records. Patient Mrs. H, 33 years old, came to the polyclinic with pain when urinating for 2 days, and nausea that had been felt for 7 days. The patient was diagnosed with UTI and Dyspepsia. Interventions were carried out in the form of providing health promotion using health posters regarding UTI and dyspepsia. The results of the intervention in patients were increased knowledge about the disease and compliance in implementing hygiene patterns, regular eating patterns, physical activity and reduced complaints experienced by patients. Holistic management can improve the knowledge, attitudes and behavior of patients and families in maintaining health.